Dissipation of the insecticides pirimiphos-methyl and dichlorvos in stored maize (Zea mays L.) grains - Strada, Julieta (2020)
Fil: Strada, Julieta. Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET); Argentina.